Measurement of interfacial adhesion strength of Copper-Silicon based dielectric interfaces via laser spallation test - Young-Min Ju; Dukyong Kim; Se-Min Lee; Heuisu Kim; Daewoong Lee; Yeon-Taek Hwang; Seung Hwan Lee; Hak-Sung Kim (Applied Surface Science Advances)
In this study, the interfacial adhesion strength between copper (Cu) and dielectric films was investigated using laser spallation test. To quantitatively evaluate the interfacial strength, the compressive stress wave generated by laser pulse was precisely calibrated, and interface stress was analyzed through wave propagation simulation. The highest adhesion strength was observed in plasma-enhanced chemical vapor deposition (PECVD) silicon oxide (63.57±11.31 MPa), followed by PECVD silicon nitride (53.95±12.04 MPa) and low-pressure chemical vapor deposition (LPCVD) silicon nitride (26.06±6.44 MPa). Scanning electron microscopy with energy dispersive spectroscopy (SEM-EDS) analysis confirmed that failure consistently occurred at the Cu/dielectric interface. The relatively high adhesion of PECVD silicon oxide was attributed to both mechanical and chemical factors. Atomic force microscopy (AFM) analysis revealed its rougher surface enhances mechanical interlocking. In addition, X-ray photoelectron spectroscopy (XPS) and Fourier transform infrared (FTIR) analyses confirmed the presence of hydroxyl groups (-OH) at the interface, facilitating Cu oxidation and Cu-O bond formation. Overall, this comprehensive study provides critical understanding for improving Cu/dielectric interfacial reliability in semiconductor devices.